Influence of Job Satisfaction on Job Performance of Business Studies Teachers in Benin Municipal Areas in Nigeria - Nwadian, C. O.; Ekpenyong, L. E. (International Journal of Educational Management, 2022)
This study investigated the influence of perceived level of job satisfaction on job performance of Business Studies teachers in Benin Municipal Areas of Edo State. Four hypotheses were formulated and tested at 0.05 level of significance. Multi-stage sampling technique was adopted to draw a sample of 180 subjects from both private and public schools. The instrument used for data collection comprised of two validated questionnaires with reliability coefficient of r = 0.89 and r = 0.90 respectively. The study revealed that job satisfaction of Business Studies Teachers was low with job satisfaction index of (X=66.05). The perceived level of job performance of Business Studies Teacher was high with job performance index of X= 57.55. Their job performance did not significantly differ in relation to marital status (Z=0.580), ownership of school (Z=0.334). For variables of gender Z=3.381 and qualification F=0.874, there is significant difference. The perceived level of job satisfaction did not significantly influence the job performance of Business Studies Teachers (r = 0.134). Some suggestions were made for policy implementation to enhance both job satisfaction and performance of Business Studies Teachers in Nigeria secondary schools ceteris paribus.